POTENSI ANTIBAKTERI DAN ANTICANDIDA EKSTRAK ETANOL DAUN PEGAGAN (Centella asiatica (L) Urb.) - admin (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2016)
Leaves pegagan (Centella asiatica (L) Urb.) is one of the medicinal plants that have various properties. It can treat fever, antibacterial, hypo-allergenic, and central nervous system stimulants. Pegagan leaf can be used as an antibacterial because it contains flavonoids, saponins, steroids, terpenoids, and tannins. The purpose of this study was to investigate the antibacterial activity of ethanol extract of Centella asiatica leaf on the growth of Staphylococcus aureus and Escherichia coli as well as anticandida activity against the growth of Candida albicans. Simplicia Pegagan leaf extracted using remaseration methods with a solution of 70% ethanol. Antibacterial test method using the disc diffusion method (Kirby and Bauer Test). Concentration of test solution used was 20%, 40%, 60%, 80% and 100% extract in DMSO, with a positive control and a negative control chloramphenicol and Dimethyl sulfoxide (DMSO). anticandida test used agar diffusion method and Potato Dextrose agar (PDA) media. The concentration of the test solution was 20%, 40%, 60% and 100% extract in DMSO, ketoconazole as a positive control and negative control DMSO used. Diameter were analyzed using one-way ANOVA statistical test. The results showed that ethanol extracts of leaves pegagan (Centella asiatica (L) Urb.) concentration of 60%, 80%, and 100% have antibacterial activity against Staphylococcus aureus and Escherichia coli. Anticandida test concentration of ethanol extract of Centella asiatica leaf provides the greatest inhibition zone is a concentration of 60%. The ethanol extract of leaves pegagan (Centella asiatica (L) Urb.) qualitatively contains flavonoids, saponins and tannins.